KETANGGUHAN PEDAGANG PASAR BABADAN-SEMARANG DI TENGAH KEPUNGAN EKONOMI GLOBAL PADA 2013-2023 - Wijayati, Putri Agus; Pratiwi, Ardela Iga; Utami, Carolina Santi Muji (Candrasangkala: Jurnal Pendidikan dan Sejarah, 2024)
The spread of modern concept market development in Indonesia at the end of the 20th century was the cause of the weakening of the empowerment of traditional market traders. Twenty years later, to be precise in the first two decades of the 21st century, advances in digital technology accelerated to penetrate all elements of life in world society. The world becomes folded in the hands of a space and time that is not limited, including borderless in the world of markets. Shopping behavior via digital platforms, whether Shopee, Tik Tok Shop, Lazada, Zalora, is a sign of an era where shopping can be realized anywhere and anytime. This reality is different from traditional markets which interact and transact factually. As a traditional market, Babadan Market in Semarang Regency has been in operation for almost a century. Babadan Market is a pillar of community economic development, because of its ability to accommodate small-scale entrepreneurs, not just in the trader category, but also in the basket category. This article aims to reveal and then identify the socio-cultural values contained in the world of Babadan's "morning" market. Socio-cultural values in any shape or form are unable to stop the market boom.